Evaluation of the environmental conditions and impacts of the exploitation and exploitation of gold minerals through dredges in the Yaguas river-Putumayo river basin - Iglesias León, Silvia (2000)
The research focuses on the environmental problems generated by informal gold mining by dredges in the Peruvian Amazon, specifically the Yaguas River Putumayo River Basin. Monitoring results effected between 09 and 15 September 1,999, show mercury in river sediments Yaguas (0.3189 and 0.3911 mg Hg / kg), which proves the technical basis for the ability of mercury deposition. The vessels (dredgers) that perform the extraction of gold does not meet the essential environmental standards set by the MEM. As urges broader assessment involving the determination of the toxicity of mercury in the ecosystem of the area through conventional water quality parameters and sediment considered in addition to, or confirming biomarkers negate the hypothesis on the introduction of mercury into the chain and its arrival at the man.